Post-divorce parenting responsibility for custody of the children: a comparative study between Shariah and Nigerian law - Abeebllahi Obalowu, Issah (Al Hikmah Research and Publication Centre, 2022)
The suffering of Muslim children in Nigeria after divorce is undeniable, as it is a phenomenon that is very widespread throughout the nation, though there is no official survey and accurate statistics about the percentage of victims of this phenomenon among children. However, the realities and some documented incidents via various means strongly confirm this painful phenomenon and its negative impact on individuals and society. Likewise, some scientific studies based on random samples have proven this fact. Therefore, this research aims to address this issue by conducting a comparative study between Islamic law and Nigerian law on parental responsibility towards children after divorce regarding their sponsorship and upbringing. The research also investigates the validity of these laws in meeting the needs of the children before and after divorce, and the extent to which these laws are realistically applied among Nigerian Muslims. Due to the nature of the study, the inductive and analytical methods are used, where information is collected from the sources, and then studied and analyzed according to the academic research method. The interviews are also conducted with people related to the topic of the research. The research arrives at several results, including the following: (1) The agreement of Islamic law and Nigerian family laws on the obligation of the children's custodianship, but the responsibility rests with the man in Islamic law, so he must facilitate and ease the means of upbringing his children. However, the Nigerian law did not clearly differentiate between the spouses in terms of who must bear the responsibility. (2) Islamic law prioritizes the spiritual aspect while considering the interests of the children, so Islam is one of the major conditions of entitlement to children’s custody, and non-Muslim mother will be therefore deprived of custody of her child after divorce, according to the opinion of the majority of scholars in Islam. It is also revealed that many fathers do not fulfill their legal duties towards their children after divorce.